Socioeconomic Outcome and Quality of Life in Adults after Status Epilepticus: A Multicenter, Longitudinal, Matched Case–Control Analysis from Germany - Kortland, Lena-Marie; Knake, Susanne; von Podewils, Felix; Rosenow, Felix; Strzelczyk, Adam (Frontiers in Neurology, 2017)
Background There is a lack of data concerning socioeconomic outcome and quality of life (QoL) in patients after status epilepticus (SE) in Germany. Patients and methods Adult patients treated between 2011 and 2015 due to SE at the university hospitals in Frankfurt, Greifswald, and Marburg were asked to fill out a questionnaire regarding long-term outcome of at least 3 months after discharge. The SE cohort consisted of 25.9% patients with an acute symptomatic, 42% with a remote symptomatic and previous epilepsy, 22.2% with a new-onset remote symptomatic, and 9.9% with other or unknown etiology. A matched case–control analysis was applied for comparison with patients with drug refractory epilepsy and seizure remission, both not previously affected by SE. Results A total of 81 patients (mean age: 58.7 ± 18.0 years; 58% female) participated. A non-refractory course was present in 59.3%, while 27.2% had a refractory SE (RSE) and 13.6% had a superrefractory SE (SRSE). Before admission, a favorable modified Rankin Scale (mRS) of 0–3 was found in 82.7% (67/81), deteriorating to 38.3% (31/81) (p = 0.003) at discharge. The majority returned home [51.9% (42/81)], 32.1% entered a rehabilitation facility, while 12.3% were transferred to a nursing home and 3.7% to another hospital. The overall mRS at follow-up did not change; 61.8% (45/74) reached an mRS of 0–3. In RSE and SRSE, the proportion with a favorable mRS increased from 45.5% at discharge to 70% at follow-up, while QoL was comparable to a non-refractory SE course. Matched epilepsy controls in seizure remission were treated with a lower mean number of anticonvulsants (1.3 ± 0.7) compared to controls with drug refractory epilepsy (1.9 ± 0.8; p < 0.001) or SE (1.9 ± 1.1; p < 0.001). A major depression was found in 32.8% of patients with SE and in 36.8% of drug refractory epilepsy, but only in 20.3% of patients in seizure remission. QoL was reduced in all categories (QOLIE-31) in SE patients in comparison with patients in seizure remission, but was comparable to patients with drug refractory epilepsy. Discussion Patients after SE show substantial impairments in their QoL and daily life activities. However, in the long term, patients with RSE and SRSE had a relatively favorable outcome comparable to that of patients with a non-refractory SE course. This underlines the need for efficient therapeutic options in SE.